Implikasi Putusan Mahkamah Konstitusi Nomor 10/PUU-VI/2008 terhadap Politik Hukum Pembentukan Undang-Undang Tentang Pemilihan Umum - Nabila Tessa Malinda Thamrin; Sunny Ummul Firdaus (Res Publica: Jurnal Hukum Kebijakan Publik, 2021)
AbstractThis study describes and examines the problem, first, what is the subject of the application in the Decision of the Constitutional Court No. 10 / Law-VI/2008. Second, the implications of the Decision of the Constitutional Court No. 10/PUUVI/2008 in the Law Policy for the Creation of the Law on General Elections. This study aims to find out how far the Implementation of the Decision of the Constitutional Court No. 10/Law-VI/2008 against the legal policy of the Law on General Elections. This study uses normative legal research. The research approaches used are legislative approaches, Conceptual Approaches, Analytical Approximations, Historical Approches and Case Approaching. The results of the study show that the Decision of the Constitutional Court No. 10/Law-VI/2008 is the first conditional Constitutional Decision issued by the constitutional court. Further action on the ruling of the Constitutional Court is the act of legislative actors (positive legisture) making the legal product better and not contrary to the 1945 UUD NRI. It is necessary to formulate a law-making law on the general election that is better than the previous election in order to face the next election.Keywords: constitutional court; test of the law; general elections.